1988
DOI: 10.1007/bf00039024
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression of foreign genes in rice, wheat and soybean cells following particle bombardment

Abstract: The development of an efficient transformation system is a prerequisite for the molecular analysis of gene expression in plants. In crop plants, this development has been hindered by difficulties encountered both in whole plant regeneration from protoplasts and in the general insusceptibility of monocots to Agrobacterium-mediated transformation. We have circumvented these difficulties by transferring foreign genes directly into the intact cells (with cell walls) of three important crop plants including rice, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(51 citation statements)
references
References 28 publications
(32 reference statements)
1
49
0
Order By: Relevance
“…Previous work based on the analysis of transient gene expression has shown that microprojectiles can be used for the delivery of DNA to a wide range of intact plant cells and tissues including those from onion, maize, tobacco (13)(14)(15)(16), rice, wheat, and soybean (22). Stable transformation by particle bombardment has been shown in tobacco (16) and soybean (18).…”
mentioning
confidence: 99%
“…Previous work based on the analysis of transient gene expression has shown that microprojectiles can be used for the delivery of DNA to a wide range of intact plant cells and tissues including those from onion, maize, tobacco (13)(14)(15)(16), rice, wheat, and soybean (22). Stable transformation by particle bombardment has been shown in tobacco (16) and soybean (18).…”
mentioning
confidence: 99%
“…Reggiardo et al (1991) found that more than one bombardment per plate had deleterious effects on barley and maize cells. However, in wheat, Wang et al (1988) observed a direct relationship between an increase in the number of cells transiently expressing GUS and an increase in the number of shots per plate. …”
Section: Resultsmentioning
confidence: 94%
“…Best results were obtained at pressure of 1100 psi, target distance of 6cm and 28 Hg in vacuum. Bombarding the explants two times increased the number of cells giving transient gene expression and this could be due to the fact that multiple bombardments allow better coverage of the target areas and compensate for misfires from faulty and poorly set rupture discs as was the case in rice (Wang et al, 1988). By using the same range of sizes reported for maize , gene transfer in wheat was shown to be most efficient with microprojectiles 1.2 µm in diameter.…”
Section: Optimization Of Conditions For Dna Deliverymentioning
confidence: 97%